Capacitação em orçamento público para os docentes gestores universitários do Campus I da UFPB: por uma execução orçamentária com eficiência - Medeiros Neto, Darci (2019)
The present study deals with the necessity to implement in Campus I of the Federal University of Paraiba – UFPB – a qualification process in the area of Public Budget specically focused on training the new University Managers and leveling the knowledge of those who already have some experience in the function. Due to the particularities in the pertinent area of budget execution, this will be the main objective of our dissertation that is based on my experience as an administrative technician in the Accountant function established in the budget sector of the Center of Sciences, Human, Letters and Arts – (CCHLA) of the UFPB, contributing this way to the achievement of the University Managers of more efficiency and effectiveness with the management of public resources in a transparent and harmonious way. This study will be consolidated through bibliographic research and analysis of federal legislation, technical norms, manuals, books and articles. An approach will also be taken to topics related to Public Administration, such as the management models that already existed and contributed to our current model, we will also discuss the wide range of Public Budget in the prism of the UFPB, trying to elucidate some important points of the day to day of our University Managers, and finally we will discuss the topic Technical Capacitation, in order to highlight how the TD & E process is – training, development and education – at national and local level, and what the Pro-Rector of Personnel Management - PROGEP of this institution has been carrying out to attend to this demand. With regard to methodology, this research this research is characterized as qualitative, descriptive and exploratory, and is based on the method of inductive approach, adopting the modelo f strategic basic nature. In terms of technical procedures, is used bibliographic, documentary and field research. Given the analysis of the data and the theoretical basis of this research, we conclude that prior qualification should be implemented regarding the Budget Execution for the teachers who will assume the functions of University Managers, in order to optimize the use and application of the resources, in consonance with the provisions of Resolution 23/2012 of CONSUNI. To assist in the management activity, while the changes are not applied in UFPB, we present at the end of this research a manual with the basic knowledge about budgetary management, which can subsidize the decision making by the managers who find difficulty to assume these functions.